1997
DOI: 10.1021/ja9710520
|View full text |Cite
|
Sign up to set email alerts
|

Shell Cross-Linked Knedels:  A Synthetic Study of the Factors Affecting the Dimensions and Properties of Amphiphilic Core-Shell Nanospheres

Abstract: Shell cross-linked knedels (SCK's), nanometer-sized spherical particles that are composed of a core-shell morphology, were prepared by intramicellar polymerization of side chain functionalities along the backbone of the hydrophilic block of amphiphilic polystyrene-b-poly(vinylpyridine) block copolymers organized into micellar assemblies. Control over the size of the SCK's was demonstrated through variation of the chemistry and processing conditions. The solid-state SCK diameters (from atomic force microscopy) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
297
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(303 citation statements)
references
References 29 publications
3
297
0
3
Order By: Relevance
“…They obtained cylindrical structures in water as a selective solvent for poly(ethylene oxide). Thrumond et al (1997) reported on crosslinking of the shell of amphiphilic diblock copolymer micelles. Nanometer-sized spherical particles composed of a core-shell morphology were prepared by intramicellar polymerization of side chain functionalities along the backbone of the hydrophilic block of amphiphilic polystyrene-bpoly(vininylpyridine) block copolymer organized into micellar assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…They obtained cylindrical structures in water as a selective solvent for poly(ethylene oxide). Thrumond et al (1997) reported on crosslinking of the shell of amphiphilic diblock copolymer micelles. Nanometer-sized spherical particles composed of a core-shell morphology were prepared by intramicellar polymerization of side chain functionalities along the backbone of the hydrophilic block of amphiphilic polystyrene-bpoly(vininylpyridine) block copolymer organized into micellar assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…The SCKs are prepared in a three-step process, including: (i) the synthesis of a linear amphiphilic block copolymer; (ii) self-assembly into spherical micelles in aqueous solution; (iii) stabilization by intramicellar crosslinking of functionalities located within the shell domain. The SCKs used in this study consisted of hydrophobic PS cores and hydrophilic, crosslinked p-chloromethylstyrene-quaternized PVP shells (21). SCKs prepared from polymer chains of 20 700 Da molecular weight and a ratio of PS:PVP repeat units of 1:2 have a solid-state diameter of 9 ± 3 nm and a hydrodynamic diameter of 16 ± 2 nm, determined by AFM and DLS, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Tris base (Sigma), sodium acetate (Sigma), EDTA dihydrate (Sigma) and agarose (Fisher) were used as received. The experimental details for the preparation of the SCK nanospheres are described elsewhere (21). The SCK composition consisted of a polystyrene (PS) core encapsulated within a layer of poly(4-vinyl pyridine) (PVP) that had been quaternized with 4-chloromethylstyrene to provide crosslinking throughout the shell layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[340][341][342] BCPs that have corona-forming blocks such as PI and PMVS with pendant vinyl groups within the polymer backbone have been shown to undergo Ptcatalysed hydrosilylation crosslinking with tetramethyldisiloxane and Karstedt's catalyst, 221,[343][344][345][346] or by UV-initiated crosslinking. 34,347 As a result of this shell-crosslinking, the micellar structures are essentially locked in and are preserved even if they are transferred from a corona-selective solvent into a common solvent for both blocks.…”
Section: (B) (A)mentioning
confidence: 99%